Platform for security-aware design of human-on-the-loop cyber-physical systems - Elfar, Mahmoud; Zhu, Haibei; Raghunathan, Adithya; Tay, Yi Y.; Wubbenhorst, Jeffrey; Cummings, M. L.; Pajic, Miroslav (Proceedings of the 8th International Conference on Cyber-Physical Systems, 2017)
Cyber-Physical Systems (CPS) are commonly supervisory control systems where a human-on-the-loop (HOL) supervises one or more autonomous systems, while embedded autonomy allows the operators to intermittently attend to the system and other tasks. Thus, it is imperative that the design of any security-aware CPS considers the impact of the human interaction with the system on security guarantees. Yet, there has been very little work on design of Human-CPS that promotes human situational awareness for enhanced system performance, particularly in terms of cyber-physical security and real-time defense against attacks. One of the main obstacles to the rapid advancement of this field is the scarcity of testbeds for evaluating security-aware Human-CPS interactions. We present RESCHU-SA, an extendable virtual platform that facilitates studying the impact that HOL has on security of CPS with varying levels of autonomy. It allows users to analyze how inductive reasoning and ability to provide context, particularly during an attack, affects the overall CPS security guarantees. The proposed platform is an extension of the Research Environment for Supervisory Control of Heterogeneous Unmanned Vehicles (RESCHU) simulation environment, previously used in various applications including studies focused on supervising Unmanned Aerial Vehicles (UAVs) missions and evaluation of interface usability.